KAJIAN IMPLEMENTASI - Messah, Yunita A.; Bolu Tena, Yohana; Udiana, I Made (Jurnal Teknik Sipil, 2012)
The complexity of the construction work, the risk of workplace accidents become higher, so the Health and Safety Work Management System (SMK3) important to be implemented in the construction company. Therefore, it is necessary to know how far the extent of implementation SMK3 especially in construction services company in Kupang City. This study used the questionnaire. The result of questionnaires data collection is processed using the Normalization de Boer formula and analyzed with concept of Traffic Light System. The survey results revealed that the percentage of SMK3 implementation in construction services company in Kota Kupang is 62.38% (yellow category) and the accident rate is on the green category. This explained that SMK3 implementations are at level 2 (safe enough). Based on the type of company, BUMN enterprises have SMK3 implementation of 87.10% and domestic private firms by 56.06%. SMK3 implementation for 5-10 year-old company at 47.85%, 10-20 years-old company at 54.18%, and the company aged > 20 years at 79.74%. The provisions of SMK3 largely have been done by construction companies. The ten provisions have been done mostly are applied of the K3 set policy, identify the hazards that will occur, to provide funds for the implementation of K3, control determines the risk of accidents, regulations made under the laws of K3, P3K facilities in sufficient quantity, create goals and objectives to be achieved, all parties involved in construction services companies should play a role in maintaining and controlling the implementation of the K3, the division of duties and responsibilities are clear and the implementation of controls to manage risks K3.